Nexus between financial literacy and financial inclusion: Examining the moderating role of cognition from a developing country perspective - Okello Candiya Bongomin, George; Munene, John C.; Mpeera Ntayi, Joseph; Akol Malinga, Charles (International Journal of Bank Marketing, 2018)
Premised on the argument that cognition structures the way how individuals think and make decisions, the purpose of this paper is to test the interaction effect of cognition in the relationship between financial literacy and financial inclusion of the poor in rural Uganda. Design/methodology/approach – The study used cross-sectional research design and quantitative data were collected and analyzed using Statistical Package for Social Sciences. Baron and Kenny guidelines were adopted to test for existence of moderating effect of cognition in the relationship between financial literacy and financial inclusion of the poor in rural Uganda. Furthermore, ModGraph excel software was used to establish the magnitude of moderating effect of cognition in the relationship between financial literacy and financial inclusion of the poor in rural Uganda. Findings – The results revealed that cognition significantly moderate the relationship between financial literacy and financial inclusion of the poor in rural Uganda. In addition, both cognition and financial literacy also have direct effects on financial inclusion of the poor in rural Uganda. Research limitations/implications – The study adopted cross-sectional research design and data were collected by use of only questionnaires. Future studies through longitudinal research design may be employed. Besides, further studies using interviews may be adopted. Furthermore, this study collected data from only tier 3 financial institutions, thus, ignoring the other financial institutions. Future studies could focus on financial institutions under the other tiers. Practical implications – The findings from the study enlightens policy-makers, managers of financial institutions, and financial inclusion advocates on the importance of cognition in enhancing financial literacy among the poor, especially in rural Uganda. Cognition combined with financial literacy helps the poor to make wise financial decisions and choices toward consuming financial services and products provided by formal financial institutions. This leads to increased scope of financial inclusion of the poor in rural Uganda. Therefore, advocates of financial literacy should assess community cultural cognition and utilize them to design and fashion effective financial literacy interventions that can promote financial inclusion. Originality/value – The study uses Baron and Kenny and ModGraph excel software to test for the interaction effect of cognition in the relationship between financial literacy and financial inclusion of the poor in rural Uganda. While several studies exist worldwide on financial inclusion, this study is the first to test the interaction effect of cognition in the relationship between financial literacy and financial inclusion of the poor in rural areas in a developing country context.
Keywords: Financial inclusion; Moderating effect; Financial literacy; Poor households; Cultural cognition; Procedural and declarative memories